2009
DOI: 10.1038/aps.2008.25
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of geniposide against hydrogen peroxide induced PC12 cells injury: involvement of PI3 kinase signal pathway

Abstract: These results demonstrate that the PI3K signaling pathway is involved in the neuroprotection of geniposide in PC12 cells against the oxidative damage induced by H(2)O(2) in PC12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 33 publications
0
89
0
2
Order By: Relevance
“…27) In our previous works, we reported that geniposide, a novel agonist for GLP-1R, prevented PC12 cells from oxidative damage via activation of glucagons-like peptide 1 receptor (GLP-1R), and induced PC12 cell neuronal differentiation via MAP kinase pathway. [10][11][12] Recently, we found that in glp-1r knockout PC12 cells, the neuroprotection of geniposide was inhibited significantly, suggesting that GLP-1R plays a critical role in the neuroprotection of geniposide and attenuates oxidative insults in these cells. 32) These neurotrophic/neuroprotective actions are in accordance with previous findings establishing that GLP-1R stimulation protects hippocampal neurons from amyloid-b peptide, Fe 2ϩ , and glutamate induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27) In our previous works, we reported that geniposide, a novel agonist for GLP-1R, prevented PC12 cells from oxidative damage via activation of glucagons-like peptide 1 receptor (GLP-1R), and induced PC12 cell neuronal differentiation via MAP kinase pathway. [10][11][12] Recently, we found that in glp-1r knockout PC12 cells, the neuroprotection of geniposide was inhibited significantly, suggesting that GLP-1R plays a critical role in the neuroprotection of geniposide and attenuates oxidative insults in these cells. 32) These neurotrophic/neuroprotective actions are in accordance with previous findings establishing that GLP-1R stimulation protects hippocampal neurons from amyloid-b peptide, Fe 2ϩ , and glutamate induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The cell viability was assessed with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as described before. 11,12) To determine whether PI3K signaling pathway is involved in the cytoprotective effect of geniposide, LY294002, a selective inhibitor of PI3K, was used, which was added to cell cultures 30 min before treatment with SIN-1. Control neurons were treated with the appropriate amount of vehicle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies have shown that geniposide possesses in vitro antioxidant activity under oxidative stress induced by hydrogen peroxide [27,28] , we first investigated whether geniposide inhibited high glucose-induced ROS overproduction. In our study, exposure of endothelial cells to high glucose resulted in increased levels of intracellular ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that the Akt signaling pathway responds to oxidative stress [95] and exerts a neuroprotective function [96,97]. Moreover, a large number of studies in vitro have illustrated that pharmacological compounds that protect cells against oxidative stress exert their neuroprotective effects through activation of the Akt pathway [98][99][100][101][102]. www.fhc.viamedica.pl Activated Akt can modulate the expression of proteins influencing cell death, such as inhibitors of apoptosis Bcl-2 and Bcl-XL or inducers of apoptosis Bax, Bad [103,104].…”
Section: Discussionmentioning
confidence: 99%